Tabungan emas di perbankan syariah Indonesia: Memenuhi kebutuhan investasi sesuai prinsip syariah dengan manajemen risiko efektif - Jauhari, Ahmad (Maliki Interdisciplinary Journal, 2024)
Gold savings are a popular investment option, particularly in Islamic banking in Indonesia, where they not only fulfill customers’ Sharia-compliant investment needs but also necessitate effective risk management. This article explores risk management implementation in gold savings at Bank Syariah Indonesia, discussing strategies to enhance investment security and customer trust. It emphasizes the importance of continuous monitoring, strengthening supervision systems, ongoing education for staff, and collaboration with external auditors. These measures ensure compliance with Sharia principles and bolster customer confidence in Sharia-based investments.